2016
DOI: 10.1117/12.2231758
|View full text |Cite
|
Sign up to set email alerts
|

Lumped element kinetic inductance detectors for space applications

Abstract: Kinetic Inductance Detectors (KID) are now routinely used in ground-based telescopes. Large arrays, deployed in formats up to kilopixels, exhibit state-of-the-art performance at millimeter (e.g. 120-300 GHz, NIKA and NIKA2 on the IRAM 30-meters) and sub-millimeter (e.g. 350-850 GHz AMKID on APEX) wavelengths. In view of future utilizations above the atmosphere, we have studied in detail the interaction of ionizing particles with LEKID (Lumped Element KID) arrays. We have constructed a dedicated cryogenic setup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The functions of this mesh are i) to absorb radiation not coupled to the antenna but scattered into the chip, thus preventing this stray radiation from coupling to other pixels (Yates et al, in prep. ); and ii) to absorb high energy phonons resulting from cosmic ray interactions as demonstrated by Monfardini et al (2016). The mesh design is optimised for radiation absorption in the 850-GHz frequency range, and to be fully transparent at the 4−6 GHz MKID frequency.…”
Section: Detector Array Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of this mesh are i) to absorb radiation not coupled to the antenna but scattered into the chip, thus preventing this stray radiation from coupling to other pixels (Yates et al, in prep. ); and ii) to absorb high energy phonons resulting from cosmic ray interactions as demonstrated by Monfardini et al (2016). The mesh design is optimised for radiation absorption in the 850-GHz frequency range, and to be fully transparent at the 4−6 GHz MKID frequency.…”
Section: Detector Array Design and Fabricationmentioning
confidence: 99%
“…In the case of the MKID detector array discussed in this paper it is possible that, in the absence of any countermeasures, a single interaction on the detector chip will result in a glitch visible over the entire area of the detector chip: Swenson et al (2010) has shown that this is exactly what happens in a small array of MKIDs. Monfardini et al (2016) recently demonstrated that it is possible to harden MKID arrays against cosmic ray events by adding a layer of a superconducting material with a critical temperature below that of the aluminium of the MKIDs: the general idea is that non-thermal (high-energy) phonons, created by the initial interaction and subsequent phonon down-conversion, are converted to phonons with an energy E < 2∆ Al through electron-phonon interactions in the low-temperature superconducting layer. The MKID array presented here has a low Tc substoichiometric TiN mesh to absorb stray radiation as discussed in Sect.…”
Section: Cosmic Ray Effectsmentioning
confidence: 99%
“…This simple scaling results in an estimated loss in integration time about 0.6% for the leaky lens design that is 30 times smaller than the solid substrate array. It is possible to harden KID arrays against cosmic ray events by adding a layer of a superconducting material with a critical temperature below the one of the aluminium of the KIDs [ 15 ]. The non-thermal (high-energy) phonons created by the initial interaction and subsequent phonon downconversion are converted to phonons with an energy E < 2 through electron–phonon interactions in the low-temperature superconducting layer.…”
Section: Interaction Between the Detector Array And Cosmic Raysmentioning
confidence: 99%
“…To further mitigate the data loss due to CR impacts, a solution has already been proposed [43]. This is based on the deposition, on the same wafer where the KID arrays are fabricated, of layers of a superconducting material having a critical temperature lower than the one of the material used for the detectors themselves.…”
Section: Kid Susceptibility To Cosmic Raysmentioning
confidence: 99%